Redemption in kind and mutual fund liquidity management - Vikas Agarwal; Honglin Ren; Ke Shen; Haibei Zhao (University of Cologne, Centre for Financial Research (CFR), 2021)
Open-end mutual funds can use redemption in kind to satisfy investor redemptions by delivering securities instead of cash. We find that funds that reserve their rightsto redeem in kind experience less redemption after poor performance. Evidence from actual in-kind transactions reveals several unique mechanisms for redemption in kind to mitigate fund runs, including the delivery of more illiquid stocks and stocks with greater tax overhang.Funds also suffer less from the adverse impact of outflows on their performance.On the other hand, redeeming investors bear significant liquidation costs when they are forced to sell securities on their own.
Keywords: G23; G28; 330; redemption in kind; mutual funds; liquidity management; financial fragility